(untitled) - Middleman, Stanley (New York, 1998)
This textbook provides more than sufficient material to support a one-semester course in fluid dynamics; for curricula that present fluid dynamics in a single quarter, there is an abundance of teaching material.
Keywords: Fluid dynamics; Mathematical models